Capacity Enhancement of Catfish Farmers through Herbal Immunostimulant Training as a Preventive Strategy in Gelang Village, Sidoarjo: Penguatan Kapasitas Pembudidaya Ikan Lele melalui Pelatihan Imunostimulan Herbal sebagai Strategi Preventif Penyakit Kuning di Desa Gelang, Sidoarjo - Dewi Nurmalita Suseno; Tri Ari Setyastuti; Budi Rianto Wahidi; Nisa Hakimah; Era Insivitawati; Shara Jayanti; Anja Asmarany R; Budi Sugianti (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Jaundice remains a recurrent problem in small-scale catfish aquaculture and contributes to reduced market value and economic losses for farmers. This community service program aimed to enhance the capacity of catfish farmers in Gelang Village, Tulangan District, Sidoarjo Regency, in producing and utilizing herbal immunostimulants as a preventive strategy. The program involved 10 farmers and was implemented through technical training consisting of theoretical sessions, hands-on practice, and mentoring. The immunostimulant introduced was prepared using a simple decoction method from locally available ingredients including Terminalia catappa, ginger, galangal, turmeric, and Curcuma xanthorrhiza. Quantitative evaluation showed an average knowledge increase of 147 percent from pre-test to post-test, with all participants exceeding the minimum improvement target. Practical skill assessment indicated an average mastery score of 94 percent, and 100 percent of participants were able to independently produce the extract. The readiness to adopt the technology reached an average score of 93 percent. Field observations indicated perceived effectiveness in supporting preventive health management practices. However, no laboratory analysis or biological measurements were conducted. This program primarily strengthened farmers’ knowledge, technical skills, and adoption readiness toward locally based preventive approaches that may support sustainable small-scale catfish farming.